👤

a=/-2√3/³:(2√12-√3)
b=(x-5)²-2(x²-25)+(x+5)²
Dau coroana!!!!!!!!


Răspuns :

[tex]a = | - 2 \sqrt{3} | {}^{3} \div (2 \sqrt{12} - \sqrt{3} ) = > a = (2 \sqrt{3} ) {}^{3} \div (4 \sqrt{3} - \sqrt{3} ) = > a = (2 \sqrt{3} ) { }^{3} \div (3 \sqrt{3} ) = > a = \frac{(2 \sqrt{3}) { }^{3} {}^{} }{3 \sqrt{3} } = > a = \frac{8 \times 3 \sqrt{3} }{3 \sqrt{3} } = > a = 8.[/tex]

[tex]b = (x - 5) {}^{2} - 2( {x}^{2} - 25) +(x + 5 {)}^{2} = > b = {x}^{2} - 10x + 25 - 2x {}^{2} + 50 + {x}^{2} + 10x + 25 = > b = {x}^{2} + 25 - 2x {}^{2} + 50 + x {}^{2} + 25 = > b = 0 + 25 + 50 + 25 = > b = 0 + 100 = > b = 100.[/tex]